152k views
4 votes
V−6(−3v+3) how do i do this and can you show me with work

User KTT
by
5.7k points

2 Answers

3 votes

Answer:

V=6;v=1

Explanation:

(V-6)(-3v+3)

-3v^2+3v+18v-18

-3v^2+21v-18

Multiple it by minus one we will get

3v^3-21v+18

Now breaking by midterm

3v^2-18v-3v+18

3v(v-6)-3(v-6)

(V-6)(3v-3)

V=6;v=1

User Lalli
by
6.3k points
3 votes

Answer:

19v - 18

Explanation:

Hello!

v - 6(-3v + 3)

Distribute the -6

-6 * -3v = 18v

-6 * 3 = -18

v + 18v -18

Combine like terms

19v - 18

The answer is 19v - 18

Hope this helps!

User Romie
by
6.3k points